A GPI processing phospholipase A2, PGAP6, modulates Nodal signaling in embryos by shedding CRIPTO - Lee, Gun-Hee (J Cell Biol, 2016)
Glycosylphosphatidylinositol-anchored proteins (GPI-APs) can be shed from the cell membrane by GPI cleavage. In this study, we report a novel GPI-processing enzyme, termed post-glycosylphosphatidylinositol attachment to proteins 6 (PGAP6), which is a GPI-specific phospholipase A2 mainly localized at the cell surface. CRIPTO, a GPI-AP, which plays critical roles in early embryonic development by acting as a Nodal coreceptor, is a highly sensitive substrate of PGAP6, whereas CRYPTIC, a close homologue of CRIPTO, is not sensitive. CRIPTO processed by PGAP6 was released as a lysophosphatidylinositol-bearing form, which is further cleaved by phospholipase D. CRIPTO shed by PGAP6 was active as a coreceptor in Nodal signaling, whereas cell-associated CRIPTO activity was reduced when PGAP6 was expressed. Homozygous Pgap6 knockout mice showed defects in early embryonic development, particularly in the formation of the anterior–posterior axis, which are common features with Cripto knockout embryos. These results suggest PGAP6 plays a critical role in Nodal signaling modulation through CRIPTO shedding.